Social Support among the Elderly Living in Shahroud, Iran - Azarnivand 1, Maryam; Alizadeh 1, Fahimeh; Soltani 1, Zeinab; Hojjati 1, Hadi; Dadgari 2, Ali; Emamian 3*, Mohammad Hassan (Shahroud Journal of Medical Sciences, 2019)
Background: Social support is one of the key aspects of social health among the elderly, significantly affecting other aspects of health. This study attempted to explore the extent to which the elderly benefit from social support and the contributing factors among the elderly living in Shahroud, northeastern Iran.Methods: During 2015-2016,a total of 496 elderly residents of Shahroud were selected through randomcluster sampling method. Data were collected by a questionnaire for capturing demographic variables (age, sex, marital status, educational level, number of children and grandchildren, economic status, health status, diseases) and Lubben Social Network Scale (LSNS). The data were analyzed through independent t-test, simple and multiple linear regressions, and ANOVA.Results:Of the 496 elderly participants in the study, 273 (55.3%) were female with a mean age of 67.9±7.84 years old. The mean score of social support achieved by the elderly was 9.0, ranging from 8.19-9.81 at the confidence interval of 95%. There was no significant relationship between age and social support (p=0.9). However, there was a significant relationship between social support and marital status. The difference in the average score of social support in married elderly was significantly less than that of single, widow(er), and divorced elderly (p<0.001).Conclusion: The elderly in Shahroud were poorly covered by social support. In order to improve this situation, it is crucial to devise appropriate plans on family to population scale.